2022
DOI: 10.4018/ijmcmc.297963
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Autoencoder-Based Hybrid Recommender System

Abstract: Recommender systems build their suggestions on rating data, given explicitly or implicitly by users on items. These ratings create a huge sparse user-item rating matrix which opens two challenges for researchers on the field. The first challenge is the sparsity of the rating matrix and the second one is the scalability of the data. This article proposes a hybrid recommender system based on deep autoencoder to learn the user interests and reconstruct the missing ratings. Then, SVD++ decomposition is employed, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A deep autoencoder is powerful for reducing the data dimensions. Bougteb et al [18] helped accurately fill in the missing data values. The autoencoder learns the user's interest, reconstructs the user's missing ratings, and then uses singular value decomposition (SVD)++ decomposition to hold information on correlation; it also provides a deep analysis of the top N recommendation items.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A deep autoencoder is powerful for reducing the data dimensions. Bougteb et al [18] helped accurately fill in the missing data values. The autoencoder learns the user's interest, reconstructs the user's missing ratings, and then uses singular value decomposition (SVD)++ decomposition to hold information on correlation; it also provides a deep analysis of the top N recommendation items.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al. [11], investigated a hybrid recommender system that combines a deep autoencoder for learning user interests and reconstructing missing ratings, along with SVD++ decomposition to capture correlations between different feature factors. In paper [12] Kamble studied the performance of recommender systems by leveraging data mining techniques by using an SVM-based recommender system and conducts experiments on various product datasets.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Studies have shown that the relevance of recommended items for a specific user is dependent on various criteria that the user considers when making a decision [8,18]. Furthermore, the use of multiple criteria can also help address the issue of the cold start problem, which arises when there is insufficient data to make recommendations for new users or items [19]. Therefore, incorporating multicriteria rating systems into recommendation systems can lead to more effective and personalized recommendations for users.…”
Section: Related Work 21 Multi-criteria Recommender Systemsmentioning
confidence: 99%
“…Additionally, DL has been applied in the field of text mining for topics detection and classification [37]. Furthermore, DL has been used in developing recommender systems, where it has achieved impressive performance in predicting user preferences and providing personalized recommendations [19,23,[38][39][40]. In particular, due to the capacity to automatically encode the representation of learnt features and the ability to perform more sophisticated nonlinear transformations.…”
Section: Deep Learning-based Recommender Systemsmentioning
confidence: 99%